Simply voracious ebook - Pearce, Kate (2011)
Wicked secrets and sensual delights abound at Madame Helene's Pleasure House—an elite brothel in Regency England that caters to carnal seduction. . . A Scent Of Scandal Lucinda Haymore is still reeling from the cruel betrayal of a vile seducer. Softly, irresistibly, his profession of love disguised his truer, baser intentions. With the knowledge that her reputation is at stake, she is happy to accept a proposal of marriage in name only from her best friend since childhood. . . A Taste Of Sin While Paul St. Clare has no interest in consummating his marriage with Lucinda, he has every intention of allowing her to enjoy true physical ecstasy in the hands of another. It's no surprise that he finds an agent more than willing to accommodate his needs in the House of Pleasure. What he doesn't expect is how perfectly the arrangement satisfies everyone's desires. . . "Can you say HOT? From the first scorching page to the last. . .a wild ride." — Simply Romance Reviews on Simply Sexual